PELATIHAN DIGITAL MARKETING DAN OPTIMALISASI MEDIA SOSIAL UNTUK MENINGKATKAN PENJUALAN UMKM DI KABUPATEN SIDOARJO - Abdullah Zailani (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
The development of digital technology has transformed marketing patterns from conventional to digital-based. However, many Micro, Small, and Medium Enterprises (MSMEs) are still unable to optimally utilize digital media to increase sales and expand market reach. This community service activity aims to improve the competence of MSMEs in utilizing digital marketing and social media as a means of product promotion. The activity implementation methods include initial observation, training, mentoring, digital marketing content creation practices, and evaluation of activity results. The activity participated in 30 MSMEs operating in the culinary, fashion, and handicraft sectors in Sidoarjo Regency. The material provided covered digital marketing concepts, marketing strategies through social media, techniques for creating engaging content, using business features on Instagram and Facebook, and optimizing WhatsApp Business. The activity results showed an increase in participants' understanding of digital marketing from an average pre-test score of 58.4 to 84.7 in the post-test. In addition, participants were able to create more professional business accounts, compile content calendars, and implement digital marketing strategies independently. This activity has had a positive impact on improving MSME marketing capabilities and is expected to support increased business competitiveness in the digital era.